'I've got you under my skin' – The role of ethical consideration in the (non-) acceptance of insideables in the workplace. (February 2019) - Gauttier, Stéphanie
Abstract: This study examines the press coverage of initiatives taken by three companies, in three different countries, to propose chip implants to their employees (' insideable' technology). The study sought to identify prevalent topics, the motivations and measures taken by the companies, the drivers and barriers of employees towards the chips, and the issues raised by experts in the newspaper articles. Content analysis was performed, with each Case being analysed separately. Then, overarching themes and differences are observed. The ethical considerations driving perception of technology have to do with privacy, the proportionality principle, harm and safety. People accepting the technology do not mention such constructs, they focus on the possibility of being pioneers and the convenience offered by the technology. Societal acceptance, through the gaze of others and the infrastructure developed in the different countries to use microchips, also plays a role to drive personal and work-related acceptance of insideables. A modelling to investigate the acceptance of insideables taking into account different dimensions of acceptability is proposed. Highlights: The role of ethical acceptability in technology (non)-acceptance is under researched. The ethical issues identified by laymen with chip implants in the workplace are broader than privacy. A new framework to study the (non)-acceptance of insideables is proposed.